I'll go and come back - LaRocca, Rajani (Candlewick Press, 2022)
Jyoti is overwhelmed when she visits her grandmother in India for the first time, but she and Sita Pati quickly form a bond. When Pati visits Jyoti in America, it is Jyoti's turn to help her grandmother feel welcome.